Evolution of an innovation network in tourism: Towards sectoral innovation eco-system - Metka Stare; Dejan Križaj (Amfiteatru Economic Journal, 2018)
Networks broaden the space for sourcing knowledge and skills for innovation in tourism beyond traditional actors and provide the framework for interactions, cooperation and knowledge sharing among them. The research focuses on complex relationships between the actors linked via web platform in generating ideas and implementing innovation in tourism. It assesses the dynamics of web platform evolution towards sectoral innovation eco-system in tourism. Applying case study methodology and unique data set we analyse the Bank of Tourism Potentials in Slovenia (BTPS), a web platform for the promotion of innovation in tourism. BTPS is considered an organizational innovation that leverages innovation in tourism and results in a number of new services, processes and business models. The originality of the paper derives from an in-depth analysis of actors' networking, collaboration and mutual learning in implementing innovation. The characteristics of interactions between actors translate into the emerging patterns of BTPS development and suggest that the web platform is assuming the characteristics of the innovation eco-system in tourism that can be transferred to other environments as well. Finally, areas of future research are proposed.
Keywords: L17; L83; O32; Z32; 330; innovation platform; networking; open innovation; collaboration; knowledge sharing; innovation eco-system